Analisis Tingkat Kepuasan Kerja Karyawan di PT PEI Menggunakan Metode Skala Likert: Analysis of Employee Job Satisfaction Level at PT PEI Using the Likert Scale Method - Mellan Assyahra Shafira; Frida Aprilia; Sonny Fransisco Siboro (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This research investigates the level of employee job satisfaction at PT Pendanaan Efek Indonesia, recognizing its crucial importance in the middle of 4.0 era as a fundamental aspect of company operations. Job satisfaction, defined as employees' positive emotional attitudes towards their work, significantly impacts performance and retention. This study aims to (1) analyze the level of employee job satisfaction based on Likert Scale measurements, and (2) identify the factors influencing this satisfaction. Employing a non-statistical quantitative method with a 5-score Likert Scale questionnaire, data was directly collected from 50 respondents. The results indicate that, overall, employees at PT Pendanaan Efek Indonesia demonstrate a good level of job satisfaction, with an average percentage of 86.16% for intrinsic factors and 95.96% for extrinsic factors. Nevertheless, several indicators still require attention, such as career development opportunities (lack of training programs), interpersonal relationships (insufficient effective communication across departments), working conditions (high workload), and salary and compensation (below industry standards and a less transparent reward system). These findings suggest the need for regular evaluation and policies that can strengthen employees' intrinsic motivation.